ANALISIS PENGARUH FAKTOR-FAKTOR BEBAN KERJA TERHADAP KINERJA TENAGA KESEHATAN PADA MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS SALOTUNGO KABUPATEN SOPPENG - Ramadana N, Amina; Rahmawati Azis, Rahmawati Azis; Muhammad Syafar, Muhammad Syafar (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Puskesmas is a Community Health Center that organizes public health efforts and first-level individual efforts. To improve the performance of health workers so that they can provide maximum service, of course it is influenced by the workload they feel. The aim of this research is to analyze the influence of Workload on the Performance of Health Workers During the Covid-19 Pandemic in the Working Area of ​​the Salotungo Health Center, Soppeng Regency. This research uses a design. Observational Cross Sectional Study with a sampling technique using the total sampling method with a total sample of 73 respondents. Based on the research results, it was found that motivation with ρ 0.001 and work environment with ρ 0.010 had an effect on the performance of health workers during the Covid-19 pandemic in the Salotungo Community Health Center work area. Soppeng Regency, while age with ρ 0.084, gender with ρ 0.243, perception with ρ 0.200, task load with ρ 0.547 and work organization with ρ 0.624 have no influence. Based on multivariate analysis, motivation is the most influential variable.